SELF-ESTEEM OF PARAFOLCLÓRICA DANCE PRACTITIONER´S AND OF BALLROOM DANCE PRACTITIONER´S (Fiep Bulletin - online, 2011)
The present study has investigated the self-esteem of adolescents of both genders, in the "parafolclórica" dance practitioner's of Colégio Madre Francisca Lampel from Gaspar (SC-Brazil) and the ballroom dance practitioner's of the academy Promenade from Porto (Portugal). This study is characterized as a field study of the descriptive type of case. The sample is consisted of 28 adolescents from 13-17 years of both genders, practiticioner's of parafolclórica dance of Colégio Madre Francisca Lampel from the city of Gaspar (SC) and 20 adolescents' practitioners of ballroom dancing competition of the Promenade Academy from Porto (Portugal). We used a structured form for the practitioners of parafolclórica dance and ballroom dance: characterization and personal self-esteem (Stobaus, 1983); Data were collected by the researcher and individually, with the practitioners of dance. Quantitative data were analyzed using descriptive statistics (frequency distribution and absolute measures of central tendency), and qualitative data through content analysis and presented in tabular form, tables and figures.
Keywords: adolescence; self-esteem; dance